Efektivitas Perangkat Pembelajaran Terintegrasi STEM terhadap Kemampuan Berpikir Kritis Siswa - Riris Nurhilyatuz Zulfa; Mohammad Masykuri; Maridi Maridi (Universitas Indraprasta PGRI Jakarta, 2022)
There are problems in SMP Negeri 8 Surakarta where student’s critical thinking skills are still low and need to be improved. Thissresearch and development.aims to find.out the effectiveness of lesson.plan integrated.STEM in material temperature and its changes to improve student’s critical thinking. This research using 4D.research procedure by Thiagarajan. Phase 4D consists of defining,.designing,.developing, and disseminating. The subjects of the study were class VII in odd semester 2021/2022 academic year in SMP Negeri 8 Surakarta which were divided into 2 classes, namely the experimental class and the control class by using a sampling technique that was simple random sampling. Data analysis in this research was analysis of improvement of critical thinking skill through N-gain test. The results shows that theelesson plan integrated STEM is effective in improving critical thinking skills because the average of experimental.class is.higher thannthe control class.